OPTIMIZATION OF ANDALAS ENDOPHYTIC FUNGI FERMENTATION CONDITIONS (Morus macroura Miq.) ISOLATE CEB 6 TO PRODUCE ANTIBACTERIAL COMPOUNDS - Yolanda, Putri; handayani, Dezi (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Fermentation optimization is an optimum condition in the fermentation process. The factors that influence the success of the fermentation process in producing secondary metabolites are temperature, pH, and the fermentation medium. The fermentation factors create the optimum conditions for the production of secondary metabolites by microorganisms. isolate CEB 6 isolated from the stem of the andalas plant was an isolate that had the ability to inhibit E.coli and S.aureus. CEB 6 isolate is one of the isolates that has a large enough potential. This study aims to determine the optimum fermentation time, the optimum pH of fermentation and the optimum temperature of fermentation. This research is a descriptive study, which was conducted from September 2020 - April 2021 at the Research Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, UNP. There were CEB 6 isolates with 3 observation groups, namely the optimum fermentation time, the optimum fermentation pH and the optimum fermentation temperature. The results showed that the optimization of the fermentation time of the endophytic fungi M. macroura Miq. CEB 6 isolates on the 6th day with the highest average inhibition zone against S. aureus that is 9,9 mm and the highest average inhibition zone against E. coli is 8,8 mm. In the optimization of optimal fermentation pH at pH 8 with an average of the highest inhibition zone against S. aureus that is 7,4 mm and an average of the highest inhibition zone against E. coli is 7,5 mm. Meanwhile, the optimal fermentation temperature optimization in an air-conditioned room (26oC) with the highest average inhibition zone against S. aureus is 7,0 mm and the highest average inhibition zone against E. coli is 8,1 mm.